Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
The vertex form of a quadratic is given by
y = a(x – h)^2 + k, where (h, k) is the vertex ;
In your case , ( - 4 , 3 ) is the vertex ;
y = a(x – h)^2 + k, where (h, k) is the vertex ;
In your case , ( - 4 , 3 ) is the vertex ;
k(x) = 2(x + 4)² + 3
k(x) = 2(x + 4)(x + 4) + 3
k(x) = 2(x² + 4x + 4x + 16) + 3
k(x) = 2(x² + 8x + 16) + 3
k(x) = 2(x²) + 2(8x) + 2(16) + 3
k(x) = 2x² + 16x + 32 + 3
k(x) = 2x² + 16x + 35
2x² + 16x + 35 = 0
x = -(16) +/- √((16)² - 4(2)(35))
2(2)
x = -16 +/- √(256 - 280)
4
x = -16 +/- √(-24)
4
x = -16 +/- 2i√(6)
4
x = -4 + 0.5i√(6)
x = -4 + 0.5i√(6) x = -4 - 0.5i√(6)
k(x) = 2x² + 16x + 35
k(-4 + 0.5i√(6)) = 2(-4 + 0.5i√(6))² + 16(-4 + 0.5i√(6)) + 35
k(-4 + 0.5i√(6)) = 2(-4 + 0.5i√(6))(-4 + 0.5i√(6)) + 16(-4) + 16(0.5i√(6)) + 35
k(-4 + 0.5i√(6)) = 2(16 - 2i√(6) - 2√(6) + 0.25i²√(36)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 0.25i²(6)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5i²) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√(1²)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√(1 × 1)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√1) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-1)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) - 1.5) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16) - 2(4i√(6)) - 2(1.5) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 32 - 8i√(6) - 3 - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 32 - 3 - 64 + 35 - 8i√(6) + 8i√(6)
k(-4 + 0.5i√(6)) = 29 - 64 + 35 + 0i√(6)
k(-4 + 0.5i√(6)) = -35 + 35 + 0
k(-4 + 0.5i√(6)) = 0 + 0
k(-4 + 0,5i√(6)) = 0
(x, k(x)) = (-4 + 0.5i√(6), 0)
or
k(x) = 2x² + 16x + 35
k(-4 - 0.5i√(6)) = 2(-4 - 0.5i√(6))² + 16(-4 - 0.5i√(6)) + 35
k(-4 - 0.5i√(6)) = 2(-4 - 0.5i√(6))(-4 - 0.5i√(6)) + 16(-4) - 16(0.5i√(6)) + 35
k(-4 - 0.5i√(6)) = 2(16 + 2i√(6) + 2i√(6) + 0.25i²√(36)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 0.25i²(6)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5i²) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1²)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1 × 1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) - 1.5) - 64 - 8i√(6) + 35
k(-4 - 0.45i√(6)) = 2(16) + 2(4i√(6)) - 2(1.5) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 32 + 8i√(6) - 3 - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 32 - 3 - 64 + 35 + 8i√(6) - 8i√(6)
k(-4 - 0.5i√(6)) = 29 - 64 + 35 + 0i√(6)
k(-4 - 0.5i√(6)) = -35 + 35 + 0
f(-4 - 0.5i√(6)) = 0 + 0
f(-4 - 0.5i√(6)) = 0
(x, k(x)) = (-4 - 0.5i√(6), 0)
The point of the graph is (-4 + 0.5i√(6), 0), or (-4 + 0.5i√(6), 0) and (-4 - 0.5i√(6),0). The vertex of the graph is (-4, 3).
k(x) = 2(x + 4)(x + 4) + 3
k(x) = 2(x² + 4x + 4x + 16) + 3
k(x) = 2(x² + 8x + 16) + 3
k(x) = 2(x²) + 2(8x) + 2(16) + 3
k(x) = 2x² + 16x + 32 + 3
k(x) = 2x² + 16x + 35
2x² + 16x + 35 = 0
x = -(16) +/- √((16)² - 4(2)(35))
2(2)
x = -16 +/- √(256 - 280)
4
x = -16 +/- √(-24)
4
x = -16 +/- 2i√(6)
4
x = -4 + 0.5i√(6)
x = -4 + 0.5i√(6) x = -4 - 0.5i√(6)
k(x) = 2x² + 16x + 35
k(-4 + 0.5i√(6)) = 2(-4 + 0.5i√(6))² + 16(-4 + 0.5i√(6)) + 35
k(-4 + 0.5i√(6)) = 2(-4 + 0.5i√(6))(-4 + 0.5i√(6)) + 16(-4) + 16(0.5i√(6)) + 35
k(-4 + 0.5i√(6)) = 2(16 - 2i√(6) - 2√(6) + 0.25i²√(36)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 0.25i²(6)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5i²) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√(1²)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√(1 × 1)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-√1) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) + 1.5(-1)) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16 - 4i√(6) - 1.5) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 2(16) - 2(4i√(6)) - 2(1.5) - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 32 - 8i√(6) - 3 - 64 + 8i√(6) + 35
k(-4 + 0.5i√(6)) = 32 - 3 - 64 + 35 - 8i√(6) + 8i√(6)
k(-4 + 0.5i√(6)) = 29 - 64 + 35 + 0i√(6)
k(-4 + 0.5i√(6)) = -35 + 35 + 0
k(-4 + 0.5i√(6)) = 0 + 0
k(-4 + 0,5i√(6)) = 0
(x, k(x)) = (-4 + 0.5i√(6), 0)
or
k(x) = 2x² + 16x + 35
k(-4 - 0.5i√(6)) = 2(-4 - 0.5i√(6))² + 16(-4 - 0.5i√(6)) + 35
k(-4 - 0.5i√(6)) = 2(-4 - 0.5i√(6))(-4 - 0.5i√(6)) + 16(-4) - 16(0.5i√(6)) + 35
k(-4 - 0.5i√(6)) = 2(16 + 2i√(6) + 2i√(6) + 0.25i²√(36)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 0.25i²(6)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5i²) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1²)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1 × 1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-√(1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) + 1.5(-1)) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 2(16 + 4i√(6) - 1.5) - 64 - 8i√(6) + 35
k(-4 - 0.45i√(6)) = 2(16) + 2(4i√(6)) - 2(1.5) - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 32 + 8i√(6) - 3 - 64 - 8i√(6) + 35
k(-4 - 0.5i√(6)) = 32 - 3 - 64 + 35 + 8i√(6) - 8i√(6)
k(-4 - 0.5i√(6)) = 29 - 64 + 35 + 0i√(6)
k(-4 - 0.5i√(6)) = -35 + 35 + 0
f(-4 - 0.5i√(6)) = 0 + 0
f(-4 - 0.5i√(6)) = 0
(x, k(x)) = (-4 - 0.5i√(6), 0)
The point of the graph is (-4 + 0.5i√(6), 0), or (-4 + 0.5i√(6), 0) and (-4 - 0.5i√(6),0). The vertex of the graph is (-4, 3).
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.